Analysis of Student Learning Motivation using Project-Based Learning Method - Muhammad Supian Sauri; Yoppy Wahyu Purnomo; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to ascertain student motivation for learning in the Elementary Mathematics Education Research Course by utilizing the Project-Based Learning (PjBL) method. The sample for this study is made up of 37 PGSD students at Yogyakarta State University. The data collection methods used were observation, a questionnaire focused on student motivation to learn, and student-led project evaluation. The data analysis technique employed is descriptive statistical analysis. The findings indicated that students' motivation for learning elementary mathematics research subjects was high, and their projects were excellent.